2009
DOI: 10.1037/a0013788
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision in treatment transport: Effects on adherence and outcomes.

Abstract: This non-experimental study used Mixed-Effects Regression Models (MRMs) to examine relations among supervisor adherence to a clinical supervision protocol, therapist adherence, and changes in the behavior and functioning of youth with serious antisocial behavior treated with an empirically supported treatment (i.e., Multisystemic Therapy), one-year post treatment. Participants were 1979 youth and families treated by 429 clinicians across 45 provider organizations in North America. Four dimensions of clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
180
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(182 citation statements)
references
References 70 publications
2
180
0
Order By: Relevance
“…Some research suggests that staffing models-at least live-in staff compared to rotating shift staff-affects a youth's experience in group care (Jones et al 2007). Live-in family staff may provide a more family-like environment that more closely approximates foster care than programs that rely on staff changes every 8 h. In addition to staffing models, staff qualifications, selection, training, supervision, and retention are important components of program quality and appear related to child-level outcomes (Schoenwald et al 2009). …”
Section: Staffingmentioning
confidence: 98%
“…Some research suggests that staffing models-at least live-in staff compared to rotating shift staff-affects a youth's experience in group care (Jones et al 2007). Live-in family staff may provide a more family-like environment that more closely approximates foster care than programs that rely on staff changes every 8 h. In addition to staffing models, staff qualifications, selection, training, supervision, and retention are important components of program quality and appear related to child-level outcomes (Schoenwald et al 2009). …”
Section: Staffingmentioning
confidence: 98%
“…Given the reality that most agencies who provide mental health services to the population generally receive little on-the-job supervision, while having to contend with an increasingly complex workplace (multidisciplinary teams addressing increasingly complex client presentations), the need for regular quality supervision, competency-based supervision training and interdisciplinary competency training are paramount (Bogo et al, 2011;Hoge et al, 2011;Schoenwald et al, 2009). However, how this can be achieved remains a challenge.…”
Section: Discussionmentioning
confidence: 97%
“…A recent systematic review (Wheeler & Richards, 2007) indicates that, while the quality of the evidence is variable, supervision appears to consistently demonstrate some positive impact on the supervisee as well as on client outcomes, when the latter are measured. For example, a recent study showed that supervisor focus on adherence to treatment principles predicted greater therapist adherence, and that two further aspects of supervision (adherence to the structure and process of supervision, and focus on clinician development) predicted change in client behavior (Schoenwald et al, 2009). Lastly, a meta-analysis interested in the impact of giving supervision feedback to clinicians about their client's progress demonstrated a more significant positive impact on client outcomes for those who showed a poor initial response to treatment (Lambert et al, 2003).…”
Section: Research On Clinical Supervision: What Makes Supervision Effmentioning
confidence: 96%
“…Some training studies have incorporated rating scale feedback to therapists (Martino et al 2008;Schoenwald et al 2008), and some data suggest that when therapists and supervisors are provided with feedback on therapist adherence, supervisor behavior may be associated with changes in therapist adherence and with changes in client behavior (Schoenwald et al 2009). Availability of feasibly administered and scored measures of therapist behavior could help facilitate further investigation in these areas.…”
Section: Utility Of Therapist Behavior Assessments In Research and Prmentioning
confidence: 98%